How safe are central counterparties in derivatives markets? - Young, H; Paddrik, M (University of Oxford, 2017)
We propose a general framework for estimating the vulnerability to default by a central counterparty (CCP) in derivatives markets. Unlike conventional stress testing approaches, which estimate the ability of a CCP to withstand nonpayment by its two largest counterparties, we study the direct and indirect eects of nonpayment by members and/or their clients through the full network of exposures. We illustrate the approach for the U.S. credit default swaps market under shocks that are similar in magnitude to the Federal Reserve's stress tests. The analysis indicates that conventional stress testing approaches may underestimate the potential vulnerability of the main CCP for this market.